An Analysis Of Using English Sentence Structures Of Indonesian Tour Guides In Prambanan Temple - Ike Anisa (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
English is considered as one of important languages in human life. Recently, English is a requirement for working people, and one of the working fields which require their employees to master English is tour guide. This research is a descriptive qualitative research which described the English sentences used by Indonesian tour guide in Prambanan temple. This research investigated their competency in producing English sentences. This study focused on the percentage of correct and incorrect sentences produces by Indonesian tour guides in Prambanan Temple. The writer finds that each respondent produced three types of sentences, which are simple sentences, compound sentences and complex sentences. Based on the analysis, each respondent produced more simple sentences than other types of sentences. Keywords: Sentence, Tour Guide